Realizing Restitution Justice for Child Victims of Sexual Assault - Hidaya, Wahab Aznul; Rakia, A. Sakti R.S.; Kora, Paulinus; Ali, Muhammad; Tuasikal, Hadi (JURNAL USM LAW REVIEW, 2024)
Children who are victims of crime often face severe challenges in their recovery after the incident. In the context of the Indonesian criminal justice system, protecting their rights is still an issue that has not been fully resolved. This study aims to analyze the procedures and considerations of judges in determining the amount of compensation for victims, especially children, who are victims of crime. The normative method examines relevant legal regulations and related legal principles. The analysis shows that the regulation on restitution for child victims has provided a systematic framework to ensure fair compensation. However, there are still challenges in effectively implementing restitution, especially in cases of sexual assault, where offenders often struggle to fulfil their restitution obligations. It creates injustice for victims, who have to bear the brunt of financial and emotional losses. In this context, the role of the judge is crucial in determining the amount of restitution appropriate to the loss suffered by the victim. The protection of child victims of crime is not only the responsibility of the criminal justice system but also of the entire society. Therefore, further measures are needed to increase public awareness and support in victim recovery, as well as to ensure that the criminal law system is more humane and progressive in protecting the rights of victims, especially the rights of children.